化简:a-(3ab+b)+(3a-4b-ab)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:14:37
化简:a-(3ab+b)+(3a-4b-ab)化简:a-(3ab+b)+(3a-4b-ab)化简:a-(3ab+b)+(3a-4b-ab)a-(3ab+b)+(3a-4b-ab)=a-3ab-b+3a
化简:a-(3ab+b)+(3a-4b-ab)
化简:a-(3ab+b)+(3a-4b-ab)
化简:a-(3ab+b)+(3a-4b-ab)
a-(3ab+b)+(3a-4b-ab)
=a-3ab-b+3a-4b-ab
=4a-4ab-5b
a-(3ab+b)+(3a-4b-ab)
=a-3ab-b+3a-4b-ab
=4a-4ab-5b
化简:a-(3ab+b)+(3a-4b-ab)
(a-b)^3-4ab(b-a)
(a-b)^3-4ab(b-a)
(a-b)3-4ab(b-a)
规定一种新运算,a*b=a+b,a#b=a-b,其中,a,b为有理数,化简a²b*3ab+5a²b#4ab结果为 ( )A 6a²b+ab B -4a²b+7ab C 4a²b-7ab D 6a²b-ab
(a b)^3-4ab
化简[(a-b)/(a+2b)]/[(a^2-b^2)/(a^2+4ab+b^2)]-(3a^2-4ab)/(a^2+ab)
化简ab-3a+4b+8
(a-b)^3+2ab(a-b)
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
化简(a^4+b^4+2a^2b^2)/(a^3+a^2b+ab^2+b^3)
1/4a^2b^2{3ab(a+b)-5a(ab-b^2)}=?
a^2b-ab+2ab^2-5a^b-4ab+3ab^2化简快
化简7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
化简7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
(a+3b)(a*a-3ab+9b*b)-(a-3b)(a*a+3ab+9b*b)
化简:5(3a^2b-ab^2)-4(-ab^2+3a^2b)
因式分解 a^4-a^3b-ab^3+b^4